Analysis of the molecular subtypes and prognostic models of anoikis-related genes in colorectal cancer - Shen, Lei; Hou, Kang; Zhang, Jifeng; Li, Xiaodong (Frontiers in Oncology, 2025)
BackgroundColorectal cancer (CRC) is a malignant tumor originating from the epithelial cells of colon or rectum. Currently, the main treatment strategy is surgery with chemotherapy and radiotherapy, but the 5-year survival rate is only 63%. Therefore, new therapeutic targets should be discovered and identified to improve survival. This study explored the critical role of anoikis-related genes in CRC development, investigated the regulatory mechanism and identified potential therapeutic drugs using data from the TCGA database, offering a theoretical foundation for CRC diagnosis and treatment.MethodsAnoikis-related genes differentially expressed in CRC tissues compared to normal tissues were identified using data from the TCGA dataset. Prognostic gene signatures were constructed using both univariate and multivariate Cox regression models. Validation of target gene expression was performed by Western blotting and qRT-PCR. To elucidate the regularity mechanisms underlying the identified gene signature, KEGG, GO, immune infiltration analysis and ssGSEA were conducted. Additionally, various computational algorithms were employed to evaluate the immunotherapeutic responses of different risk groups. The oncoPredict package predicted candidate chemotherapy agents.ResultsBased on screening and identification results, we established three anoikis-related genes: LEP, HAMP, and FAM43B, as the prognostic prediction genes of CRC. We successfully constructed the study model and demonstrated that the risk score of the anoikis-related prognostic prediction signature is an independent prognostic factor in overall survival. Additionally, the results of immune microenvironment infiltration showed that the high-risk score group had a greater infiltration of the M0, M1, and M2 macrophages. In the immunotherapy cohort, the prognosis of patients with a high score, as judged by the study model, was significantly better. The risk score of the anoikis-related prognostic prediction gene is associated with the immunotherapy response in metastatic colorectal cancer.ConclusionsOur study reports on the identification of anoikis-related gene subtypes and the construction of a prognostic signature in CRC, which, in turn, can provide a basis for further study of the molecular mechanism, clinical diagnosis, and treatment of CRC.